NEW YORK CITY COUNCIL HEARING ON SMOKING - CHILCOTE,SD JR (Tufts Archival Research Center, 2007)
Testimony of Brennan Moran, Tobacco Institute, at New York City Council Hearing on Smoking, 28 October, 1987. Lists allies as business, labor, entertainment, tourism, and minority communities. Questions scientific evidence regarding environmental tobacco smoke. Accuses smoking act of restricting personal freedom and private business autonomy. Predicts act will be economically burdensome.